Design of fiberglass rescue boat by using waste plastic bottles - Zanatul Nadia, Zakaria (2010)
This thesis describes the design of fiberglass rescue boat by using waste plastic bottles. Fiberglass layer of rescue boat has tendency to crack when hit by a heavy wave or involves in accident. As an alternative of this problem, waste plastic disposal has been reuse to fill the displaced volume of the designed rescue boat. The main objective of this thesis is to design a fiberglass rescue boat that has arrangement of bottles under the waterline section of the designed rescue boat. Lines plan of the rescue boat and general arrangement has been designed to visualize the design. Several analyses on the design have been made to show the compatible of the design. This thesis described methodology utilized, design software and final lines plan and general arrangement of the designed rescue boat. From the results, it is observed that the rescue boat use 303 waste plastic bottles to fit the displaced volume of the fiber glass rescue boat. The displaced volume of the rescue boat is 1156 kg. The design rescue compatible for 6 persons on an average weight of 100 kg, 12.0261 kg for the total weight of waste plastic bottles arrangement, boat’s engine and storage tanker of the rescue boat on the rescue boat at one time.